Pengaruh Pertumbuhan Ekonomi dan Inflasi Terhadap Pertumbuhan Kredit UMKM Indonesia Periode 2015-2022 - Zahara, Vadilla Mutia; Anwaruddin, Fadli; Mangara, Togi Haidat (Universitas Labuhanbatu, 2023)
Micro, Small and Medium Enterprises is an important sector in the Indonesian economy. Micro, Small and Medium Enterprises have a very important role in improving people's welfare and creating jobs. However, Micro, Small and Medium Enterprises also face various obstacles, such as limited access to capital, limited access to information, and limited market access. This scientific study aims to examine the impact of economic growth and inflation on MSME credit growth in Indonesia during the 2015-2022 period. This scientific study uses the method of multiple linear regression analysis with secondary data originating from the Financial Services Authority, the Central Bureau of Statistics, and Bank Indonesia Â and processed using the Eviews application. The results of the analysis show that economic growth and inflation have no effect and are not significant on the growth of MSMEs credit in Indonesia during the study period.